Colobomatus gymnoscopeli sp.n. (Copepoda: Philichthyidae), a parasite of lateral line sensory canals of Gymnoscopelus aphya Günther, 1873 (Myctophidae) from the Antarctic waters - J. Grabda; T. Linkowski (Acta Ichthyologica et Piscatoria, 1978)
A new species, Colobomatus gymnoscopeli is described; data on its location in the host species, Gymnoscopelus aphya (Myctophidae), invasion incidence, intensity, and geographical distribution in the Antarctic waters are given. The host specificity of the Colobomatus Hesse, 1873 species is discussed.